Safety considerations for withdrawal of nucleos(t)ide analogues in patients with chronic hepatitis B: First, do no harm - Yao-Chun Hsu; Cheng-Hao Tseng; Jia-Horng Kao (Clinical and Molecular Hepatology, 2023)
Nucleos(t)ide analogues (NA) are widely used to treat hepatitis B virus (HBV) infection, but they cannot eradicate the virus and treatment duration can be lifelong if the endpoint is set at seroclearance of the hepatitis B surface antigen (HBsAg). As an alternative strategy, finite NA therapy without the prerequisite of HBsAg seroclearance has been proposed to allow treatment cessation in patients with sustained undetectable HBV viremia for two to three years. However, reactivation of viral replication almost always follows NA withdrawal. Whereas HBV reactivation might facilitate HBsAg seroclearance in some, it could lead to serious acute flare-ups in a certain proportion of patients. Occurrence and consequences of NA withdrawal flares are complicated with various factors involving the virus, host, and treatment. Accurate risk prediction for severe flares following NA cessation is essential to ensure patient safety. The risks of life-threatening flares in patients who discontinued NA according to the stopping rules of current guidelines or local reimbursement policies have recently been quantitatively estimated in large-scale studies, which also provided empirical evidence to help identify vulnerable patients at risk of devastating outcomes. Moreover, risk predictors were further explored and validated to hopefully aid in patient selection and management. In this narrative review with a focus on patient safety, we summarize and discuss current literature on the incidence of severe flares following NA cessation, risk stratification for candidate selection, rules of posttreatment monitoring, and indications for treatment resumption. We also share our thoughts on the limitations of existing knowledge and suggestions for future research.